Computer-aided design and fabrication of microstrip low-pass filter/ Zulkifli Mohd Sidi - Mohd Sidi, Zulkifli (1999)
The purpose of this project is to design, simulate, fabricate and measure the characteristics of a microstrip low-pass filter operating at microwave frequencies using computer-aided design (CAD) package. The filter was designed to have minimum return loss of 15 dB over the frequency range of 0-2 GHz and minimum attenuation of 15dB at 3 GHz. The type of this filter is called maximally flat or Butterworth filter, which has less delay distortion than other type of microwave filters [1]. The microstrip laminates used are 'Duroid/Rogers 5872' with a 0.5 mm substrate thickness and relative permittivity (er) of 2.33. A commercially available CAD suite HP Eesof Touchstone Libra was utilised to eliminate tedious processes associated with conventional filter design methods. The circuit was fabricated using facilities available at the faculty. The filter characteristics were determined using a Wiltron 562 Scalar Network Analyser.